Highly Efficient, Fast, Room Temperature Synthesis of Tetrahydrobenzo[b]pyrans Catalyzed by Zn[(L)-proline]2 as Green and Reusable Heterogeneous Catalyst Under Dry Grinding - Montazeri, Naser; Pourshamsian, Khalil; Keshavarzi, Shabnaz; Montazer Rezaei, Batool (Asian Journal of Chemistry, 2012)
An easy method for the synthesis of tetrahydrobenzo[b]pyrans through a one-pot three-component reaction of dimedone, aryl aldehydes and malononitrile under mild reaction conditions using Zn[(L)-proline]2 as catalyst is described. The products were obtained in short reaction times with excellent yields at room temperature under dry grinding. The catalyst could be recycled and reused for several times without noticeably decreasing the catalytic activity. It is believed that this applicability of Zn[(L)-proline]2 with mentioned advantages makes present method superior over all previous reported methods to the synthesis of tetrahydrobenzo[b]pyrans.